Anthelmintic resistance in gastrointestinal nematodes of dairy cattle in the Macalister Irrigation District of Victoria. Issue 1 (January 2016) - Bullen, SL; Beggs, DS; Mansell, PD; Runciman, DJ; Malmo, J; Playford, MC; Pyman, MF
Abstract : Objective: To report anthelmintic resistance in gastrointestinal nematode parasites of cattle on commercial dairy farms in the Macalister Irrigation District of Gippsland, Victoria. Methods: Faecal egg count reduction tests (FECRTs) were used to assess anthelmintic resistance on 20 Macalister Irrigation District dairy farms between May 2013 and June 2014. All three currently available anthelmintic classes for cattle nematodes in Australia were tested. Faecal samples were collected 10–14 days post‐treatment for individual faecal egg counts (FEC) and larval differentiation. The arithmetic mean FEC for each treatment group was compared with an untreated control post‐treatment. Resistance was defined as <95% reduction in FEC, with a lower 95% confidence interval <90% when the mean FEC of the control group, differentiated by genus, was greater than 25 eggs/g. Results: Anthelmintic resistance was present on all 20 dairy farms involved in this study. Resistance to doramectin in at least one species was detected on 15/20 (70%) farms, fenbendazole on 16/20 (80%) farms and levamisole on 5/20 (25%) farms. On three farms, resistance by Ostertagia ostertagi to all three anthelmintic classes was detected. Conclusion: This is the first report of anthelmintic‐resistant O. ostertagi on Australian dairy farms. Resistance to all three available anthelmintic classes is of concern, given the high pathogenicity of this species. The study highlights the need for veterinarians and dairy farmers to be aware of the risks posed by anthelmintic resistance.